Strong field induced ion and electron emission from size-selected metal clusters - K. Raspe; L. Kazak; N. Iwe; B. Krebs; F. Martinez; K.-H. Meiwes-Broer; J. Tiggesbäumker (Physical Review Research)
Single-sized clusters of Ag_{309}^{−} are accumulated within a digital Paul trap and exposed to intense optical laser pulses, leading to the formation of nanoplasmas of known initial conditions, not yet feasible. Using field-free diagnostics, the resulting Coulomb explosion is analyzed, giving electron distributions and charge-state resolved ion energy spectra. Experiments on the well-defined target result in comprehensive information on the particle emission and reveals details of nanoplasma dynamics not available before. These are for example the particle size-specific intensity-dependent transition towards a fully ionized plasma state as well as the subtle interplay between electron and ion dynamics, which becomes apparent in the intensity-dependent development of maximum and average values of energy and charge state.